Strategies and materials for the prevention and treatment of biofilms - Xiaoxia Kang; Xiaoxiao Yang; Yue He; Conglin Guo; Yuechen Li; Haiwei Ji; Yuling Qin; Li Wu (Materials Today Bio, 2023)
Biofilms are aggregates of organized microbial growth that function as barriers and create a stable internal environment for cell survival. The bacteria in the biofilms exhibit characteristics that are quite different from the planktonic bacteria, such as strong resistance to antibiotics and other bactericides, getting out of host immunity, and developing in harsh environments, which all contribute to the persistent and intractable treatment. Hence, there is an urgent need to develop novel materials and strategies to combat biofilms. However, most of the reviews on anti-biofilms published in recent years are based on specific fields or materials. Microorganisms are ubiquitous, except in the context of medical and health issues; however, biofilms exert detrimental effects on the advancement and progress of various fields. Therefore, this review aims to provide a comprehensive summary of effective strategies and methodologies applicable across all industries. Firstly, the process of biofilms formation was introduced to enhance our comprehension of the “enemy”. Secondly, strategies to intervene in the important links of biofilms formation were discussed, taking timely action during the early weak stages of the “enemy”. Thirdly, treatment strategies for mature biofilms were summarized to deal with biofilms that break through the defense line. Finally, several substances with antibacterial properties were presented. The review concludes with the standpoint of the author about potential developments of anti-biofilms strategies. This review may help researchers quickly understand the research progress and challenges in the field of anti-biofilms to design more efficient methods and strategies to combat biofilms.